2003
DOI: 10.1103/physrevb.68.165202
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Al–transition-metal quasicrystals

Abstract: We report on a class of icosahedral aluminum-transition-metal ͑Al-TM͒ alloys with true semiconducting behavior. Our description of the structure of these icosahedral quasicrystals is based on the six-dimensional Katz-Gratias-Boudard ͑KGB͒ model of the face-centered-icosahedral ͑fci͒ quasicrystal and its rational approximants. The shell structure of the atomic surfaces in perpendicular space defines the chemical order of aluminum and transition-metal ͑TM͒ atoms leading to semiconducting transport properties. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 48 publications
(59 reference statements)
2
36
0
1
Order By: Relevance
“…In any case, the existence of a deep pseudogap is an indication of a considerable degree of covalency in the interaction between the Al and the transition-metal atoms. 33 Previous investigations ͑both theoretical 30 and experimental 34 ͒ of the surface electronic structure of i-Al-Pd-Mn have demonstrated that the metallic character of the bonding is enhanced at the surface and that the pseudogap is partially leveled out as a consequence of a strong relaxation of the near-surface Al atoms. The present work extends these studies to the electronic structure of a well-ordered quasiperiodic adlayer and we find that the pseudogap has disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…In any case, the existence of a deep pseudogap is an indication of a considerable degree of covalency in the interaction between the Al and the transition-metal atoms. 33 Previous investigations ͑both theoretical 30 and experimental 34 ͒ of the surface electronic structure of i-Al-Pd-Mn have demonstrated that the metallic character of the bonding is enhanced at the surface and that the pseudogap is partially leveled out as a consequence of a strong relaxation of the near-surface Al atoms. The present work extends these studies to the electronic structure of a well-ordered quasiperiodic adlayer and we find that the pseudogap has disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations have been used previously 2,7,8,[17][18][19] to calculate the geometric and electronic structures of the surfaces of quasicrystalline approximants and of pseudomorphic adlayers formed on these surfaces. Using the results for the surface electronic structure, simulated STM images 13 were generated and the good agreement with experimental images confirmed the validity of the theoretical structure models.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,19 The calculations have demonstrated that unsupported quasiperiodic monolayers are not stable and that quasiperiodic ordering in an adsorbed monolayer results from the strong binding of adatoms to quasiperiodically distributed adsorption sites. 7 A Penrose P1 tiling consisting of pentagons, pentagonal stars, boats, and thin golden rhombi can be superimposed on the atomic structure of the five-fold surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Several studies have identified these cut clusters as strong adsorption sites. 7,[28][29][30][31][32] Therefore the 8.0 Å Pb pentagons might result from the preferential adsorption of adatoms at these specific sites. The motif shown in Fig flowerlike motif of the clean surface but 2 scaled.…”
Section: A Pb Adsorption On the Fivefold Surface Of The I-al-cu-fe Qmentioning
confidence: 99%